Relationship Between Government Expenditures on Health and Residents' Consumption: New Evidence From China Based on the Bootstrap Rolling-Window Causality Test - Jiang, Ting-Yu (Frontiers in Public Health, 2021)
This paper explores the necessity of expanding government expenditures on health (GEH) from the perspective of promoting residents' consumption (RC). It employs bootstrap full- and subsample rolling-window Granger causality tests to investigate the mutual causal influence between GEH and RC. It finds that GEH have a positive impact on RC in some periods and a negative impact in other periods. The positive effect from GEH to RC reveals that Chinese governments at all levels should continue to increase GEH, narrow the gap between their medical and health investments and those of developed countries', directly reduce current medical expenses of residents, and increase the immediate consumption of residents. However, this opinion cannot always be upheld because a negative impact from GEH to RC also exists. The current paper shows that the government should improve the efficiency of the use of health expenditures; effectively shorten the time lag of government health fiscal policies; and promote the positive effect of government health expenditures on RC.